(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Bell’s palsy affects facial motor functions, facial symmetry, and also results in facial disability as well as facial synkinesis. Mime therapy and motor imagery techniques play an important role in improvement of facial motor functions, symmetry, physical, social functions; reduction in facial disability and synkinesis. Objective: To compare the effects of mime therapy and motor imagery technique on facial motor functions, symmetry, disability, and synkinesis in Bell’s palsy. Methods: This study was Randomized Control Trial (parallel two arm study design). Non probability convenient sampling technique was used. Toss and coin method was used for the random allocation of participants in mime therapy and motor imagery technique groups. Patients with age 20-40 years, both male and female, patients diagnosed with BP, and paralysis/paresis of all muscles of one side of face were included. Results: There were 44 participants in this this study; mime therapy group (n=22) and motor imagery technique group (n=22). Mean age of patients was 29.75±4.97 while in mime therapy group mean age was 30.32±5.17 and in motor imagery technique Group mean age was 29.18±4.81. For House-Brackmann Scale (At 3rd week p=0.68 & at 6th week p=0.63)), Sunny-brook Facial Grading System (At 3rd week p=0.64 & at 6th week p=0.82), Facial Disability Index-Physical function(At 3rd week p=0.30 & at 6th week p=1.00), Facial Disability Index-Social function(At 3rd week p=0.53 & at 6th week p=0.81), and Synkinesis Assessment Questionnaire(At 3rd week p=0.56 & at 6th week p=0.32); no interaction was reported between time and group, there is no significant difference between mime therapy and motor imagery technique groups. Within group analysis revealed that both groups showed significant improvement individually based on facial motor function, symmetry, and disability. Both groups did not reveal significant improvement individually based on facial synkinesis. Conclusion: There is no significant difference between mime therapy and motor imagery technique groups based on facial motor functions, symmetry, synkinesis, and disability. Both groups showed significant improvement of facial symmetry, motor functions of facial muscles, and reduction in disability. Both groups did not reveal a significant improvement individually based on facial synkinesis.